Genetic diversity in the E6 and E7 gene of human papillomavirus type 16 among cervical cancer patients in Riau Province, Indonesia - Maya Savira; Rachmadina Rachmadina; Azza Enggar Mahargyarani; Muhammad Zhafran Admiral; Donel S; Amru Sofian; Renady Reza Razali; Zidny Ilmiah; Analdi Farniga (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2026)
Cervical cancer mostly occurs due to persistent high-risk human papillomavirus (HPV), with type 16 being the most frequent. In Indonesia, cervical cancer ranks second in mortality, with a fatality rate of 57%. The E6 and E7 genes of HPV-16 play crucial roles in the virus’s oncogenic transformation, leading to cervical cancer. This study was conducted to determine the prevalence and genetic diversity of the E6 and E7 genes of HPV-16 in Riau Province, Indonesia. There were 37 HPV-positive samples analyzed using the MY09/11 primers. This was followed by the amplification of the E6 and E7 genes. Nineteen samples were detected as HPV-16, thirteen of which were coinfected with HPV-18. Seven E6 and E7 sequences were aligned compared with the reference sequence NC_001526.4. The most common nucleotide changes in the E6 gene, 7318A>G, was detected in 30.7% of samples, leading to an amino acid change from 65N>S. Three nucleotide changes were identified in the E7 gene of sample 89: two synonymous (7831T>C, 7837T>G) and one non-synonymous (7989A>G), resulting in an amino acid change of 29N>S. The most frequent E7 nucleotide change, 7708G>A, was found in 80% of samples. Phylogenetic analysis revealed that HPV-16 isolates from Riau have close kinship with the European lineage, with 57.1% (E6) and 85.7% (E7). In conclusion, the incidence of cervical cancer in Riau Province caused by HPV-16 is 52.8% and 7318A>G and 7708G>A are the most common genetic diversity. Furthermore, the majority of HPV-16 isolates in Riau Province show close kinship with the European lineage.